Natural Transformation in Acinetobacter baumannii W068: A Genetic Analysis Reveals the Involvements of the CRP, XcpV, XcpW, TsaP, and TonB2 - Hu, Yuan; Zheng, Junjie; Zhang, Jianzhong (Frontiers in Microbiology, 2022)
Acinetobacter baumannii is a serious threat to public health, and there is increasing attention to the development of antibiotic resistance in this bacterium. Natural transformation is a major horizontal gene transfer mechanism that can lead to antibiotic resistance. To better understand the mechanism of natural transformation in A. baumannii, we selected a clinical isolate that was transformable but had no visible extracellular type IV pili (T4P) filaments, and then examined the effects of multiple single-gene knockouts on natural plasmid transformation. Among 33 candidate genes, 28 knockout mutants had severely or completely impaired transformability. Some of these genes had established roles in T4P biogenesis; DNA transfer across the outer membrane, periplasm, or inner membrane; and protection of intracellular ssDNA. Other genes had no previously reported roles in natural transformation of A. baumannii, including competence activator CRP, a periplasmic protein that may function in T4P assembly (TonB2), a T4P secretin-associated protein TsaP, and two T2SS minor pseudopilus assembly prime complex competent proteins (XcpV and XcpW). The deletion of the T2SS assembly platform protein XcpS had no effect on transformation, and the minor pseudopilins were capable of initiating major pilin assembly. Thus, we speculate that XcpV and XcpW may function in DNA uptake with major pilin assembly, a non-T2SS dependent mechanism, and that a competence pseudopilus similar to T4P constituted the central part of the DNA-uptake complex. These results may help guide future research to on the alarming increase of antibiotic resistance in this pathogen.